Ópera e literatura em cena: uma análise da obra juvenil aída, adaptada por han mi-ho e ilustrada por Lucia Sforza - Binato, Cláudia Penavel [UNESP]; Ferreira, Eliane Aparecida Galvão Ribeiro [UNESP] (My University, 2014)
This text’s objective is to present an analysis of Aída, adapted by Han Mi-Ho (2012) and illustrated by Lucia Sforza, from the classic eponymous opera by Giuseppe Verdi. This book is part of the collection Classical music on the scene, published by FTD, which aims to introduce stories of important librettos regarded as classics in the music field to young audiences. More specifically, we intend to verify in this text, with Bakhtinian principles, how the dialogue between Verdi’s work and HanMi-Ho’s is actualized. To achieve these objectives, we will present a reflection of what provides the pleasure in reading. In this text we built the hypothesis that Han-Mi-Ho’s strategy to rescue a classic opera and adapt it in the form of an illustrated narrative for the young reader provides the contact with an attractive and playful text that leads to critical reflection and expands his knowledge through the rescue of the cultural memory. The appropriation of a classic cultural production adapted to the narrative language and targeted to a young audience can act as an appraisal factor in the identity of the reader. Through it, he is able to raise his self-esteem, because he perceives that he is considered as a production receiver, while at the same time he is recognized as the heir of a traditional cultural heritage.

Este texto tem por objetivo apresentar uma análise da obra Aída, adaptada por Han Mi-Ho (2012) e ilustrada por Lucia Sforza, a partir de ópera clássica homônima de Giuseppe Verdi. Esta obra compõe a coleção Música clássica em cena, da editora FTD, que visa a apresentar ao público jovem histórias de importantes libretos considerados como clássicos no campo musical. Mais especificamente, pretende-se neste texto verificar, a partir dos princípios bakhtinianos, como se efetiva a dialogia entre a produção de Verdi e a obra adaptada de Han-Mi-Ho. Para a consecução dos objetivos, pretende-se apresentar uma reflexão acerca do que propicia o prazer na leitura. Constrói-se, neste texto, a hipótese de que a estratégia de Han-Mi-Ho de resgatar uma ópera clássica e adaptá-la sob a forma de narrativa ilustrada para o jovem leitor, tanto lhe faculta contato com um texto atraente, lúdico e crítico que o conduzirá à reflexão, quanto amplia seus conhecimentos, por meio do resgate da memória cultural. A apropriação de uma produção cultural clássica, mas adaptada à linguagem narrativa e direcionada ao jovem, pode atuar como fator de valoração da identidade deste leitor. Por meio dela, ele é capaz de elevar sua autoestima, pois percebe que é considerado como receptor de uma produção, ao mesmo tempo em que se reconhece como herdeiro de um patrimônio cultural tradicional.
Opera and literature on the scene: an analysis of juvenile work aída, adapted by han mi-ho and illustrated by Lucia Sforza
Keywords: Opera; Classical Culture; Cultural Heritage; Ópera; Cultura Clássica; Patrimônio Cultural